Professional Identity, Social Recognition and Entering the Workforce of the University Student with Hybrid Education - Damián, Javier (2014)
We show advances of  a research which aims to describe the factors that facilitate and hinder to entering the workforce of graduates with hybrid university education, same than those responsible for education policy assert that facilitates this type of training to graduates entering the labor market. Through a case study and a qualitative approach we studied the graduates of the Business Science Degree in a Oaxaca public university, in that mix three Bachelors traditional causing a hybrid university program. Preliminary results point to two factors that limit the employability of graduates, the lack of professional identity in the graduate unmotivated to carry out actions that promote their participation and lack of social recognition of the profession by employers for which graduates are not in demand in the local labor market; contradicting both situations-at least in the case study, the alleged advantages attributed to hybrid undergraduate programs.